Adenosine acts by A(1) receptors to stimulate release of prolactin from anterior-pituitaries in vitro - Yu, Wen H. (The National Academy of Sciences, 1998)
Adenosine has been identified in the anterior pituitary gland and is secreted from cultured folliculostellate (FS) cells. To determine whether adenosine controls the secretion of anterior pituitary hormones in vitro, adenosine was incubated with anterior pituitaries. It stimulated prolactin (PRL) release at the lowest concentration used (10(−10) M); the stimulation peaked at 10(−8) M with a threefold increase in release and declined to minimal stimulation at 10(−4) and 10(−3) M. Follicle-stimulating hormone release was maximally inhibited at 10(−8) M, whereas luteinizing hormone release was not significantly inhibited. Two selective A(1) adenosine receptor antagonists (10(−7) or 10(−5) M) had no effect on basal PRL release, but either antagonist completely blocked the response to the most effective concentration of adenosine (10(−8) M). In contrast, a highly specific A(2) receptor antagonist (10(−7) or 10(−5) M) had no effect on basal PRL release or the stimulation of PRL release induced by adenosine (10(−8) M). We conclude that adenosine acts to stimulate PRL release in vitro by activating A(1) receptors. Since the A(1) receptors decrease intracellular-free calcium, this would decrease the activation of nitric oxide synthase in the FS cells, resulting in decreased release of nitric oxide (NO). NO inhibits PRL release by activating guanylate cyclase that synthesizes cGMP from GTP; cGMP concentrations increase in the lactotrophs leading to inhibition of PRL release. In the case of adenosine, NO release from the FS cells decreases, resulting in decreased concentrations of NO in the lactotrophs, consequent decreased cGMP formation, and resultant increased PRL release.